Urgensi Pemilihan Alat Permainan Edukatif (APE) (Studi pada Guru Taman Kanak-kanak Witri I Kota Bengkulu) - fatrica Sayfri (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2016)
Games are usual for children but choosing toys hel them to decide their development of attitude, behavior, and intellegence. This article discussed about the significance of choosing tool for playing in witri I Kinder Garden Bengkulu. Based on observation and interview. those tools children to build their attitude, behaviour, and intellegence. However, the tecabers did not have format or guidance to use them in Witri I kinder Garden Bengkulu espeacially ini giving meaning for those kind of playings.